P-V Relation for Mercuric Calcogenides: Ab Initio Method - G. Misra; S. Tenguria; M. Gautam (Журнал нано- та електронної фізики)
Mercuric Calcogenides found many applications in electronic and optical devices as semiconducting materials. An equation of state provides useful information about the relationship between pressure (P), volume (V) and temperature (T) that helps to understand the behaviour of materials under the effect of high pressure and high temperature. The present paper sheds light on the electronic structure of Mercuric Calcogenides by simulating its electronic properties through ab initio method. This ab initio method is extended to derive the equation of state for Mercuric Calcogenides. The present equation of state has also been tested for the prediction of End Point. The computed results compare well with Quantum statistical data.